Rancang Bangun Edugame Pembelajaran Kesehatan Gigi untuk Anak-AnakBerbasisUNITY 3D - Theofilus Fiendi Hernowo; Evi Sulviana; Willy Willy; Hernando Ivan Teddy (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2014)
Game is a medium for playing and for most of the people it’s used as an entertainment to spend their spare time. Nevertheless, it should be better if the game used is an educational game, so that the users do not only have fun but also learn something to enrich their knowledge. Therefore, because of the reason above, the writer created an educational game base on Unity 3D about the dental health for kids, so it can be used by the users as a medium of learning to know the importance of keeping the dental health early. This educational game is created by using Unity 3D as its engine. In the process of creating this game, the writer created the character of player, 3D objects, animations and textures. Its player is an object of toothpaste that’s used by the users to play and squirt the toothpaste to the germs and bacterias. The method used to create this educational game is prototyping method and the main purpose of this game is the users can use it as a medium of learning about the importance of keeping the dental health. As the result, this educational game application can be used as a medium of learning for the users to always keep their dental health.